2005
DOI: 10.3348/kjr.2005.6.4.235
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Treatment of Extrahepatic Bile Duct Stones Assisted by Balloon Sphincteroplasty and Occlusion Balloon

Abstract: ObjectiveTo describe the technical feasibility and usefulness of extrahepatic biliary stone removal by balloon sphincteroplasty and occlusion balloon pushing.Materials and MethodsFifteen patients with extrahepatic bile duct stones were included in this study. Endoscopic stone removal was not successful in 13 patients, and two patients refused the procedure due to endoscopy phobia. At first, all patients underwent percutaneous transhepatic biliary drainage (PTBD). A few days later, through the PTBD route, ballo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Percutaneous transhepatic removal of CBD stones is a minimally invasive alternative for surgical treatment. This approach is not commonly used for patients in whom ERCP treatment is not possible and only a few studies have reported the results of this procedure [17,18,19,20,21,22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous transhepatic removal of CBD stones is a minimally invasive alternative for surgical treatment. This approach is not commonly used for patients in whom ERCP treatment is not possible and only a few studies have reported the results of this procedure [17,18,19,20,21,22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous antegrade expulsion of bile stones into the duodenum over a dilated papilla was initially described by Meranze et al [10], Muchart et al [11], and Gil et al [12] and then reported by others [2,13,14] in large series of patients. This technique is considered to be safe and effective: maintenance of the anatomic integrity and function of the sphincter is desirable, resulting in a great advantage compared with other treatment techniques, such as endoscopic papillotomy or surgery.…”
Section: Discussionmentioning
confidence: 96%
“…Frequently, prior mechanical lithotripsy is required and removal of BDS remains incomplete. Both methods revealed certain risks like pancreatitis, bleeding, or intrahepatic injury whilst concrement extraction [10, 11]. …”
Section: Discussionmentioning
confidence: 99%
“…Both techniques have been shown to be a less invasive alternative for extraction of BDS compared to surgery. Nevertheless, pancreatitis, hemorrhage, or injury of liver tissue were reported [11]. Furthermore, necessity of maintaining access to PTCD for several weeks is accompanied with marked reduction of patients comfort, quality of life, and increases costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation